Experts' Expectations of Future Vulnerability at the Peak of the "Refugee Crisis" - Bernhard Edwin Riederer (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2018)
Immigrant inflows in 2015 triggered manifold reactions all over Europe. Questions about the integration capacities of nation states dominated media coverage. Fears of negative consequences for host societies were widespread. But what did experts (scientists, practitioners, and policy-makers) think? Using 203 assessments of experts collected through a questionnaire sent in late 2015 and early 2016, the present article addresses expected effects of refugee flows on future vulnerability in European societies. As many young families and minors are among asylum-seekers, we focused on the expected development of economic, psychological and social vulnerability of families with children. On average, experts assumed that their vulnerability would increase in the context of current and future refugee flows especially in the upcoming years. In line with affectedness by displaced people (i.e. asylum applicants per inhabitant), estimations differed by country. Expected mean increases in vulnerability are largest in German-speaking and Nordic countries. With regard to long-term consequences (until 2050), a rise in social vulnerability seemed most likely indicating experts worry about stigmatisation, discrimination, and social cohesion in European societies.
Keywords: 300; Migration; asylum; refugee; vulnerability; family; inequality; future; Europe; expert opinion